Capital Inflows and Policy Responses in the As EAN Region - Koenig, Linda (IMF Working Papers; Working Paper, 1996)
This paper reviews the experience of four ASEAN countries in dealing with an unprecedently strong influx of foreign capital in the late 1980s and early 1990s. While there was some increase in inflation associated with the inflows, it was relatively minor, and real exchange rates did not appreciate. Countries responded in the first instance by using open market operations for sterilized intervention. Subsequently, the fiscal stance was tightened. There was reluctance to allow nominal currency appreciation and, with one exception, controls on capital inflows were avoided.